FUNGSI EHABLA PADA MASYARAKAT SENTANI, PAPUA - Modouw, Wigati Yektiningtyas (ATAVISME, 2007)
Ehabla is one of oral poetry in Sentani, Papua that is almost extinct. It is sung spontaneously, without background of notes and memorization. The singer prepares plot and theme that will be elaborated in the performance, Ehabla can be transcribed into 4 lines that is dominated by repetition and parallelism. The first line is repeated in the third line, the second line is repeated in the fourth line. Essentially, the third and the fourth lines are the repetition of the first and the second lines. The repetition is enriched by synonym and reduplication. Ehabla that expresses the socio-cultural life of Sentani people can be used as media of (1) education (pedagogical system) that teaches hard work, cooperation, pride, respecting tradition, proud of birthplace, respecting natural environment; (2) reflection of Sentani people's idealization on ideal village, ideal society, and ideal leaders; (3) legitimacy of traditions; (4) forcing and watching; (5) sharpening the emotion of religion and belief; and (6) entertainment. For Sentani people who live in some remote areas in some islands, the singing and function of ehabla are still responded even though its socialization is not positively responded by the young generation. For Sentani people who live near the city, the singing and function of ehabla are not again responded by both old and young generation. This is caused by the influence of new traditions, technology, and globalization. The only function that is still alive is the function of entertainment.